The impact of digitization on corporate controlling and the role of controllers - Hastenteufel, Jessica; Dorow, Max; Weber, Susanne (Managerial Economics, 2024)
Digitization is a megatrend that strongly influences organisations and is reflected in all business processes and operational functions. It is therefore not surprising that controlling is also affected by digitization. This paper first defines and explains the key sub-processes of controlling and describes the traditional role and tasks of controllers that are derived from this. Next, selected technologies such as the internet of things, big data, cloud computing and artificial intelligence are described in detail and their influence on controlling and the role of the controller is analysed. It is shown that digitization is already having a significant impact on controlling and still holds considerable potential for the future. This will also lead inevitably to a continuous refinement of the role and tasks of controllers, whereby they will have to further expand their knowledge and skills in the future.